The molluscan fauna of Chella Bank and surroundings (Western Mediterranean Sea) - José Antonio Caballero-Herrera; Javier Urra; Serge Gofas; Carmen Salas; Patricia Bárcenas; Marina Gallardo-Núñez; Elena Moya-Urbano; Jesús Olivero; José L. Rueda (Scientia Marina, 2023)
Molluscs of Chella Bank and its surroundings were studied from 21 samples collected with a van Veen grab in the depth range 95-729 m. A total of 299 taxa were identified (77 live-taken), thus increasing by more than 95% the species of molluscs reported in the recently declared site of community importance “Sur de Almería-Seco de los Olivos”. Two of the species are new records to Spanish waters and one to the Alboran Sea. The high species richness observed could be related to the location, the hydrological characteristics and the topographical heterogeneity of the area within the Alboran Sea. Four significant groups of samples were discriminated through multivariate analysis of quantitative data of live-taken molluscs: (I) bathyal muddy bottoms with buried rhodoliths; (II) bathyal muddy bottoms with coral rubble; (III) bathyal hemipelagic muddy bottoms and (IV) bathyal sandy bottoms. Molluscs were more diverse on coral framework bottoms than on sedimentary bottoms around Chella Bank. Most of the live-taken species are widely distributed along the Atlantic and Mediterranean Sea, and a few are strictly Mediterranean. The most striking feature was the occurrence of two species with planktotrophic larval development for which Chella Bank is the sole recorded locality in the Mediterranean (Episcomitra angelesae and Mitrella templadoi) and which elsewhere extremely rare (Mathilda spp.).